Daniel Gutiérrez Trápaga, Rewritings, Sequels, and Cycles in Sixteenth-Century Castilian Romances of Chivalry: “Aquella inacabable aventura” - Julio Enrique Macossay Chávez (Medievalia)
Daniel Gutiérrez Trápaga, Rewritings, Sequels, and Cycles in Sixteenth-Century Castilian Romances of Chivalry: “Aquella inacabable aventura”, Woodbridge, Tamesis, 2017, 210 pp.